Distant targets? making the 21st-century development strategy work : 1998-2015 - McGee, Rosemary; Robinson, Clive; van Diesen, Arthur (London: Christian Aid, 1998)
"Rosemary McGee, Clive Robinson, Arthur van Diesen"